2008
DOI: 10.1109/tasc.2008.920818
|View full text |Cite
|
Sign up to set email alerts
|

Development and Test of LARP Technological Quadrupole Models of TQC Series

Abstract: Abstract-In support of the development of a large-aperture Nb3Sn superconducting quadrupole for the Large Hadron Collider (LHC) luminosity upgrade, several two-layer technological quadrupole models of TQC series with 90 mm aperture and collar-based mechanical structure have been developed at Fermilab in collaboration with LBNL. This paper summarizes the results of fabrication and test of TQC02a, the second TQC model based on RRP Nb3Sn strand, and TQC02b, built with both MJR and RRP strand. The test results pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…1). This behavior could explain the performance of the latest LARP magnets based on the RRP conductor that, at 1.9 K, had equal or even lower quench currents with respect to the 4.4 K case [15], [16], [18]. Strand measurements also showed that: 1) covering the strand with a 1 mm thick layer of stycast reduced the quench current at 1.9 K of less than 10%; 2) the strand self-field stability can be improved by reducing the strand diameter or by reducing the critical current density.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…1). This behavior could explain the performance of the latest LARP magnets based on the RRP conductor that, at 1.9 K, had equal or even lower quench currents with respect to the 4.4 K case [15], [16], [18]. Strand measurements also showed that: 1) covering the strand with a 1 mm thick layer of stycast reduced the quench current at 1.9 K of less than 10%; 2) the strand self-field stability can be improved by reducing the strand diameter or by reducing the critical current density.…”
Section: Discussionmentioning
confidence: 94%
“…It was also shown [7] that for RRP strand with low RRR: 1) the minimum quench current due to the self-field instability, that is the self-field stability current , is lower at 1.9 K than at 4.2 K; 2) at 1.9 K the can be considerably lower than the critical current at 12 T. The self-field instability might be the cause of the limited quench performance at 1.9 K of the latest magnets based on the RRP conductor built by the LARP collaboration [15], [16], [18].…”
mentioning
confidence: 99%
“…ARP Technology Quadrupoles (TQ) [1,2] and all other LHC Accelerator Research Program (LARP) magnet designs [3,4] are presently based on 0.7 mm Nb 3 Sn strands. The workhorse material chosen for the next step in the magnet R&D is the 54/61 subelement (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical design Within LARP, two different mechanical design concepts are under study with the TQ series. The first one relies on stainless steel collars, iron yoke and welded stainless steel skin and is presently implemented in the TQC magnets ([1]- [6]). In this concept, all the pre-stress is applied to the coil during the collaring and the yoking process, at room temperature.…”
Section: Mechanical Analysismentioning
confidence: 99%